Effects of TMB-8 on constriction of pial arteries in rats - Wang Bin; Xiao Ji-Gao (Acta Pharmacologica Sinica; Vol 21, No 2 (February 2000): Acta Pharmacologica Sinica, 2016)
"AIM: To study the effects of 8-(N,N-diethylamino)-n-octyl-3,4,5-trimethoxybenzoate (TMB-8) on constriction of pial arteries (PA). METHODS: The change of PA in rats was observed continuously and directly through cranial window using microcircular image-shearing system. RESULTS: Nimodipine (Nim) 1 mumol.L-1 produced dilatation of PA immediately and the maximal response occurred in 2 min. But the diameter was not changed by TMB-8 50 mumol.L-1. PA diameter decreased immediately after the application of CSF containing KCl. TMB-8 25, 50 mumol.L-1 apparently inhibited KCl-induced PA constriction. When persistent constriction was evoked by 5-HT, diameter of PA were increased in a concentration-dependent manner after application of TMB-8, which was inhibited by N omega-nitro-L-arginine methyl ester (L-NAME). CONCLUSION: TMB-8 inhibited the contraction induced by 5-HT or KCl in cerebral artery, probably via its calcium antagonization and nitric oxide release."